KANDUNGAN NUTRISI BISKUIT ELA SAGU FERMENTASI DENGAN MIKRO ORGANISME LOKAL (MOL) SEBAGAI PAKAN TERNAK RUMINANSIA - Meyk, Bryan; Joseph, Godlief; Joris, Lily (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims to analyze the nutritional content waste of sago biscuits fermented using Local Micro Organisms (MOL) as an alternative ruminant died. The basic ingredient used iswaste of sago which is fermented with local micro organisms (MOL) to increase its nutritional value and digestibility as animal feed. The variables observed in this research were: crude protein, crude fiber, crude fat and ash conte nt and Beta-N and the experimental design used was a descriptive design. The research results show that fermentation with MOL can increase the nutritional content of ela sago biscuits, especially in terms of protein content and fiber digestibility, so that these biscuits have the potential to be a good additional feed for ruminants. This conclusion shows that the use of fermented sago palm with MOL as a feed ingredient can support efficiency and sustainability in feeding in ruminant farming systems.